Synthesis and characterization of microporous granular activated carbon from Silver berry seeds using ZnCl2 activation. Issue 9 (15th July 2021) - Benmahdi, Fatiha; Oulmi, Kafia; Khettaf, Sami; Kolli, Mounira; Merdrignac-Conanec, Odile; Mandin, Philippe
Abstract: Granular activated carbon (GAC) was synthesized from Silver berry ( Elaeagnus Angustifolia L. ) seeds using zinc chloride as the activation agent. To optimize the operating parameters, the effects of the time and temperature of carbonization, impregnation ratio, and heating rate on the iodine number and yield of activated carbon were studied. Optimized parameters were impregnation ratio of 1:1, carbonization temperature of 500 °C, carbonization time of 1 hour, and heating rate of 5 °C/min. The GAC synthesized under optimized conditions was characterized by Nitrogen adsorption-desorption isotherms, SEM, EDX, XRD, FT-IR, Boehm titration, TG-TGA, and TG-IR. It was found that the synthesized GAC has a microporous structure with a BET surface area of 1109 m 2 /g, a micropores volume of 0.317 cm 3 /g, and an average pore diameter of 2.1 nm. The methylene blue (MB) dye was employed as a molecule model to evaluate the porosity and the adsorption capacity of the synthesized GAC. The results showed that the maximum adsorption capacity of MB and the percent portion of the surface area (SMB /SBET ) were 120.48 mg/g and 30.62%, respectively. The experimental results reveal that the synthesized GAC can be used as a low-cost adsorbent for the removal of small and large environmental pollutants.